PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK BERTUKAR PASANGAN TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 22 PADANG - Ulil ‘Azmi, Ulil ‘Azmi; Anggraini, Villia; Cesaria, Anna (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ The background of this research is about students understanding of mathematical concepts is still low and they prefer copy answers without understand and consider its true. The aims of this research is to know the students understanding of mathematical concepts by implementing cooperative learning model pair exchange technigue is better than the students understanding of mathematical concepts by applying conventional learning in VIII grade SMPN 22 Padang. The kind of this research is experimental research by random design towards the subject. The population in this research was students in VIII grade SMPN 22 Padang in school year 2013/2014. The sample Class were chosen is VIII.8 class as experimental class and VIII.6 class as control class . The instrument which was used is final test which is essayÂ from with reliability is Â = 0.89. Based on calculations of data analysis using t-test of the side obtained = 2.50 and = 1.67 . So Â > Â thus it can be concluded that students understanding of mathematical concepts apply cooperative learning model pair exchange technique is better than the students understanding of mathematical concepts by applying conventional learning in VIII SMPN 22 Padang .